Platformizing the Sacred: Subscription-Based Qur’anic and Hadith Content in Digital Business Models - Asep Koswara; Ela Sartika; Abdul Rohman; Lina Herlina (UIN Sultan Syarif Kasim Riau, 2026)
Digital platforms are increasingly reshaping the landscape of Islamic knowledge by embedding Qur’an and Hadith within subscription-based business ecosystems. This study examines how platform-based models transform sacred texts into monetized digital services, drawing on illustrative cases such as emerging platforms like Kitabpedia and AI-assisted tools such as KhutbahAI that offer paid access to curated Islamic content. Using a qualitative approach, the research employs digital observation and critical interpretive analysis to explore the structural, epistemological, and ethical dimensions of these platforms. The findings indicate that religious knowledge is increasingly reconfigured as personalized, scalable, and commodified digital content, while religious authority undergoes a significant shift from scholar-centered legitimacy toward platform-mediated and algorithmically structured authority. In this emerging configuration, the visibility and credibility of religious knowledge are increasingly shaped not only by ulama or institutional scholarship, but also by algorithmic ranking systems and user engagement metrics. At the same time, the integration of market logic into sacred domains generates tensions related to access inequality, authenticity, and the ethical limits of monetization within Islamic business principles. The study proposes the concept of a “Platformized Sacred Economy” to capture this transformation, offering a novel analytical lens that bridges digital religion, platform capitalism, and Islamic ethics, with implications for the governance of religious content in digital environments.